As consequências do desemprego para os rendimentos de reemprego: Uma análise para diferentes condiç\~oes do mercado de trabalho - Maurício Cortez Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper aims to investigate earnings losses of workers who become unemployed in Brazil, comparing the results for different stages of the business cycle. Estimates using longitudinal data from the continuous PNAD for the period between 2012 and 2017 show that workers who transited from employment to unemployment and were reemployed during a period of strong labor market conditions experienced small and usually non-signifi cant earnings declines. However, earnings losses are estimated between 10% and 15% for those who became unemployed and were able to fi nd a new job under weak labor market conditions. Part of this reduction seems to be due to the workers fl ow to jobs in the informal sector, which is higher during periods of high unemployment rates compared to times of better labor market conditions.
Keywords: J30; J63; E24; 330; unemployment; labor earnings; labor market conditions